2022
DOI: 10.1002/1878-0261.13201
|View full text |Cite
|
Sign up to set email alerts
|

DCZ0415, a small‐molecule inhibitor targeting TRIP13, inhibits EMT and metastasis via inactivation of the FGFR4/STAT3 axis and the Wnt/β‐catenin pathway in colorectal cancer

Abstract: Thyroid receptor‐interacting protein 13 (TRIP13), a protein of the AAA‐ATPase family, is upregulated in various human cancers, including colorectal cancer (CRC). This study focused on the inhibition of TRIP13‐induced CRC progression and signalling by DCZ0415, a small molecule targeting TRIP13. It demonstrated potent antitumour activity in TRIP13‐deregulated cancer cell lines, regardless of their p53, KRAS, BRAF, epidermal growth factor receptor or microsatellite instability status. The treatment of CRC cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Overexpression of GOLT1B can increase the level of DVL2 and enhance its plasma membrane translocation, then activate the downstream Wnt/β-catenin pathway and increase the level of nuclear β-catenin, thereby inducing epithelial-mesenchymal transition (EMT) [ 112 ]. DCZ0415, a small molecule inhibitor against TRIP13, inhibits EMT and metastasis in colorectal cancer by inactivating the FGFR4/STAT3 axis and the Wnt/β-catenin pathway [ 113 ].…”
Section: Wnt Pathway-related Biochemical Processmentioning
confidence: 99%
“…Overexpression of GOLT1B can increase the level of DVL2 and enhance its plasma membrane translocation, then activate the downstream Wnt/β-catenin pathway and increase the level of nuclear β-catenin, thereby inducing epithelial-mesenchymal transition (EMT) [ 112 ]. DCZ0415, a small molecule inhibitor against TRIP13, inhibits EMT and metastasis in colorectal cancer by inactivating the FGFR4/STAT3 axis and the Wnt/β-catenin pathway [ 113 ].…”
Section: Wnt Pathway-related Biochemical Processmentioning
confidence: 99%
“…TRIP13 is implicated in EMT in lung cancer through modulation of TGF-β signaling (47,(57)(58)(59) . TRIP13 inhibition blocks EMT in colorectal cancer (46) and multiple myeloma (60) . TRIP13 modulates TGF-β-SMAD signaling in multiple disease states (57,58) , and is itself a target of TGF-β signaling in mice (63) .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of TRIP13 has been shown to promote EMT in cancer cells (45)(46)(47) and IPF AT2 cells express higher levels of mesenchymal proteins (48)(49)(50) . We hypothesized that in IPF, TRIP13 promotes AT2 cell acquisition of mesenchymal features.…”
Section: Trip13 Is Increased In Ipf Tissues and At2 Cellsmentioning
confidence: 99%
“…In the other side, c-Myc was able to induce the transcription of TRIP13[8, 12,34]. Recent discoveries have revealed that TRIP13 regulated the Wnt signaling pathway and the epithelial-mesenchymal transition in cervical cancer [35], lung cancer[36], thyroid cancer [37], colorectal cancer [32], cholangiocarcinoma[8], which could induce tumor growth and progression. While researches on TRIP13 develop fast, the prognostic value of TRIP13 in cancer is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13overexpressing cancer cells showed a signi cant increase in proliferation, invasion, and migration compared with control cells, on the contrary, depletion of TRIP13 by shRNA or TRIP13 inhibitor DCZ0415 could signi cantly inhibit cancer cell growth, induce cell apoptosis and enhance drug sensitivity [7,12,31]. Agarwal S et al have demonstrated that TRIP13 interacted with FGFR4 which could activate the EGFR-AKT pathway in colorectal cancer [11,32]. In addition, Gao Y et al have found that TRIP13 is directly bound to EGFR and modulated the EGFR signaling pathway in bladder cancer [19].…”
Section: Discussionmentioning
confidence: 99%